2009
DOI: 10.1016/j.ygyno.2009.02.011
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin expression in ovarian cancer in the laying hen, Gallus domesticus, compared to human ovarian cancer

Abstract: Objective-Epithelial ovarian carcinoma (EOC) is a leading cause of cancer deaths in women. Until recently, a significant lack of an appropriate animal model has hindered the discovery of early detection markers for ovarian cancer. The aging hen serves as an animal model because it spontaneously develops ovarian adenocarcinomas similar in histological appearance to the human disease. E-cadherin is an adherens protein that is down-regulated in many cancers, but has been shown to be up-regulated in primary human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 41 publications
6
37
0
Order By: Relevance
“…Our results support previous studies in the hen which reported increased expression of ovalbumin and E-cadherin in chicken ovarian tumors [8,38]. Ovalbumin and Ecadherin are in the list of the top 25 up-regulated genes in ovarian tumor tissue compared with normal ovarian tissue with expression levels increased >200-fold and 40-fold, respectively (Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results support previous studies in the hen which reported increased expression of ovalbumin and E-cadherin in chicken ovarian tumors [8,38]. Ovalbumin and Ecadherin are in the list of the top 25 up-regulated genes in ovarian tumor tissue compared with normal ovarian tissue with expression levels increased >200-fold and 40-fold, respectively (Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…Hens have a high incidence of ovarian cancer and, similar to women, this incidence increases with age [3]. Several studies have reported that ovarian tumors of the hens express antigens that are frequently expressed in human ovarian tumors including cytokeratin, EGFR, HER-2/neu, COX-1, VEGF, and E-cadherin [4][5][6][7][8][9]. Barua et al found that chicken tumors resemble all four phenotypes found in women, with serous and endometrioid tumors present at about equal frequencies [10].…”
Section: Introductionmentioning
confidence: 99%
“…This E-cadherin pattern could potentially have diagnostic value, but more importantly, identifying factors that regulate E-cadherin expression in the ovary may give clues as to which pathways become dysregulated very early on during the transformation of normal cells toward a malignant phenotype. We have shown previously that E-cadherin is significantly upregulated in hen ovarian cancer similar to what is observed in the human disease [12]. qPCR analysis from the current study reveals that E-cadherin mRNA is decreased more than 40% in tumors from hens fed flaxseed (Figure  5) and E-cadherin protein has been shown to be decreased by 50% in tumors from flax-fed hens [22].…”
Section: Resultssupporting
confidence: 83%
“…Moreover, the sequencing of the chicken genome 10 years ago enabled valuable molecular comparisons with human cases (71). Different biomarkers, such as CA-125, P53 and E-cadherin, were also expressed in EOC in both species (28,(72)(73)(74).…”
Section: Incessant Ovulation Hypothesismentioning
confidence: 95%